Studi Kasus Pemahaman Siswi Kelas IX terhadap Pembelajaran Teks Eksplanasi di SMP Muhammadiyah 2 Tarakan : Penelitian - Asih Riyanti; Arifo Saputra; Aqilla Salsabila; Ummu Safirah Anggriani; Rasma Junita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to observe the understanding of IX grade female students regarding explanatory texts and identify students' learning style preferences that can support their understanding. The method used in this study is qualitative analysis, because this study uses direct observation by filling out questionnaires and open-ended questions and answers to determine students' understanding. The subjects of the study consisted of 13 female students and one Indonesian language teacher at Junior High School Muhammadiyah 02 Tarakan City, with the main focus on five female students for questions and answers. The results of the study prove that most female students know and understand explanatory texts, although they still have difficulty in understanding the elements of cause and effect. The main cause of this difficulty in understanding is more influenced by their low interest in this type of text than by the teaching methods applied by the teacher. Female students' preferences for learning tend to lead to fun learning methods, such as creating texts together and doing small projects such as explanatory text presentations equipped with pictures or videos. Based on the results of the research, it is recommended to apply a variety of teaching methods that can accommodate various learning styles, in order to improve students' understanding of explanatory texts